High condylectomy versus proportional condylectomy: is secondary orthognathic surgery necessary?. Issue 1 (January 2016) - Fariña, R.; Olate, S.; Raposo, A.; Araya, I.; Alister, J.P.; Uribe, F.
Abstract: The objective of this study was to assess the need for secondary orthognathic surgery in patients undergoing two different condylectomy protocols for active unilateral condylar hyperplasia (UCH). A retrospective cohort study evaluated UCH patients treated by condylectomy. Two groups were established: group 1 comprised those who had undergone a high condylectomy (5 mm removed) and group 2 comprised those who had undergone a proportional condylectomy (removing the difference observed between the measurements of the hyperplastic and the healthy side). Data analysis was done with the Levene test and t -test; a P -value of <0.05 indicated a statistically significant relationship. Forty-nine patients, with an average age of 19.83 years, were analyzed; 11 were included in group 1 and 38 in group 2. There was no statistical difference between the two groups with regard to age or sex ( P = 0.781). An average of 5.81 mm was removed in the high condylectomy group, while an average of 9.28 mm was removed in the proportional condylectomy group; this difference was statistically significant ( P = 0.042). Comparing the two groups, proportional condylectomy reduced the need for secondary orthognathic surgery ( P < 0.001). The proportional condylectomy can be used as the sole surgical treatment in cases of UCH, thus avoiding the need for secondary orthognathic surgery.